БІЛІМ БЕРУ САЛАСЫНДА ЖҰМЫС БЕРУШІЛЕРДІҢ АКТІЛЕРІНІҢ МАҢЫЗЫ (Journal of actual problems of jurisprudence, 2019)
In article theoretical problems of employment of the population, realisation of human rights on references and conditions of acceptance ofcertificates of the employer are considered.